1982
DOI: 10.1104/pp.70.2.517
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Inorganic Carbon Usage by the Marine Cyanobacterium, Synechococcus sp

Abstract: The marine cyanobacterium, Synechococcus sp. Nageli (strain RRIMP N1) changes its affinity for external inorganic carbon used in photosynthesis, depending on the concentration of CO2 provided during growth. The high affinity for CO2 + HCO-of air-grown cells (K1/2 < 80 nanomoles [pH 8.21) would seem to be the result of the presence of an inducible mechanism which concentrates inorganic carbon (and thus C02) within the cells. Silicone-oil centrifugation experiments indicate that the inorganic carbon concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
176
2
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 14 publications
12
176
2
1
Order By: Relevance
“…4C) (Fig. 4C) was very similar to that observed for a marine species of Synechococcus in the absence of any added inhibitor (2,3,27).…”
Section: Fluorimetrysupporting
confidence: 66%
See 3 more Smart Citations
“…4C) (Fig. 4C) was very similar to that observed for a marine species of Synechococcus in the absence of any added inhibitor (2,3,27).…”
Section: Fluorimetrysupporting
confidence: 66%
“…The difference in peak height between experimental curves (+ Na2S) and the curve obtained in the dark was was made to calculate rates of CO2 transport (17). Nevertheless, the method provides an alternate means of assessing CO2 transport, as distinct from HCO3-transport, over a range of [CO2] and is the procedure most directly comparable to 4GCO2 pulsing techniques used in conjunction with silicone fluid filtering centrifugation (2,17,28) and isotopic disequilibrium experiments (6).…”
Section: Fluorimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…15,20,28), whereas air-adapted blue-green algae (2) and Scenedesmus at alkaline pH have been used to study HC03-as well as C02 uptake. The principle investigator of the DIC pump with Scenedesmus was Findenegg (6)(7)(8)(9), who showed that C02-grown, synchronized cultures ofScenedesmus, when changed to air levels of C02, formed a partial HC03-pump within 2 h in the light that functioned between pH 8 to 1.…”
mentioning
confidence: 99%